Isoverrucarol production by Fusarium oxysporum CJS-12 isolated from corn. - Kim, K H (1990)
Isoverrucarol (3,15-dihydroxy-12,13-epoxy-trichothec-9-ene) was isolated and purified from wheat cultures of a toxic strain of Fusarium oxysporum CJS-12. The toxin was characterized by thin-layer chromatography, gas chromatography-mass spectrometry, and 1H and 13C nuclear magnetic resonance spectrometry. Isoverrucarol caused toxic effects in rats, including loss of appetite, bodily weakness, severe mucosae of the stomach, and death, when administered orally at 10 and 20 mg/kg of body weight. The toxin also caused a definite dermatitic reaction of epidermis and an edematic-necrotic response of the dermis.